Structural overview of macromolecular machines involved in ribosome biogenesis. (April 2021) - Frazier, Meredith N; Pillon, Monica C; Kocaman, Seda; Gordon, Jacob; Stanley, Robin E
Highlights: Macromolecular assemblies regulate pathways through active site coordination. Ribosome biogenesis relies on higher order enzymatic machines throughout the assembly process. AAA-ATPases coordinate spatial and temporal control of large ribosomal subunit assembly. ITS2 processing uses multienzyme complexes to target pre-rRNA for degradation. Crosstalk within macromolecular machines facilitates high catalytic output and ensures specificity. Abstract : The production of ribosomes is essential for ensuring the translational capacity of cells. Because of its high energy demand ribosome production is subject to stringent cellular controls. Hundreds of ribosome assembly factors are required to facilitate assembly of nascent ribosome particles with high fidelity. Many ribosome assembly factors organize into macromolecular machines that drive complex steps of the production pathway. Recent advances in structural biology, in particular cryo-EM, have provided detailed information about the structure and function of these higher order enzymatic assemblies. Here, we summarize recent structures revealing molecular insight into these macromolecular machines with an emphasis on the interplay between discrete active sites.